A Weak Maximum Principle for Discrete Optimal Control Problems with Mixed Constraints - Andreani, Roberto; Ascona, John Frank Matos; de Oliveira, Valeriano Antunes [UNESP] (Springer Nature, 2024)
In this study, first-order necessary optimality conditions, in the form of a weak maximum principle, are derived for discrete optimal control problems with mixed equality and inequality constraints. Such conditions are achieved by using the Dubovitskii–Milyutin formalism approach. Nondegenerate conditions are obtained under the constant rank of the subspace component (CRSC) constraint qualification, which is an important generalization of both the Mangasarian–Fromovitz and constant rank constraint qualifications. Beyond its theoretical significance, CRSC has practical importance because it is closely related to the formulation of optimization algorithms. In addition, an instance of a discrete optimal control problem is presented in which CRSC holds while other stronger regularity conditions do not.
Keywords: Constant rank of the subspace component constraint qualification; Discrete maximum principle; Discrete optimal control problems; Mixed constraints; Nondegenerate necessary optimality conditions